QUALITY OF ONION CREAMS - PRATI, PATRÍCIA; BERBARI, SHIRLEY A.GARCIA; MOURA, SILVIA C. S. ROLIM DE (Revista Brasileira de Engenharia de Biossistemas, 2008)
The purpose of this research was to evaluate the effect of different conservation methods on quality of onion cream storage at room temperature (25ºC). It was tested three conservation methods for the products packed in glasses: whitening of the cream after triturating, following of hot fill; blanching of the raw material before triturating, following of exhaustion and pasteurisation; and whitening of the raw material before triturating, addition of chemical conservation and cold fill in glasses and plastic bottles packages. The final products were storage at room temperature by ninety days, and evaluated in zero time and each thirty days through colour objective analysis and sensorial analyse of the appearance, colour, odor and taste attributes. The results were evaluated by test of means (Tukey) and Anova. In respect at colour objective evaluation, all samples showed darkening during storage. The sensorial evaluations showed that only the odor reduced with signi-ficance during the storage of the CV and BA samples. The other attributes didn’t show significant changes during evaluation. The samples chemically conserved showed the better appearance and colour, important factors for the consumer.